ROLE AND SIGNIFICANCE OF INTANGIBLE RESOURCES AND ASSETS IN E-COMMERCE - S. Panasenko; V. Cheglov; A. Shishkin (Вестник Северо-Кавказского федерального университета)
He concept, types of intangible resources and assets, prerequisites for increasing their role and importance in the modern conditions of the pandemic and in the process of getting out of it (especially their own trademarks and business reputation of trade organizations), recommendations for improving the efficiency of management of intangible resources and assets of trade organizations (participating in electronic sales of goods and services), including the need to use legal instruments for the protection and protection of intellectual property rights, accounting policies, insurance, restructuring of intangible resources and monitoring the functioning environment of economic entities of trade.